Solving the problem of exploitation of transformers with corrosive sulfur by oil desulfurization using a strong inorganic base and organic solvent - Kolarski, Dejan; Janković, Jelena; Mihajlović, Draginja; Kovačević, Neda; Lukić, Jelena (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
Most of power transformer failures are associated with the presence of corrosive sulfur compounds in mineral insulating oil, of which dibenzyl disulfide (DBDS) is the best known and most widespread corrosive sulfur compound. Oils found to be the main cause of transformers failures usually contained DBDS, a compound with pronounced affinity for the formation of copper (I) sulfide (Cu2S). Copper (I) sulfide is a compound that does not dissolve in oil, conducts electricity and can be deposited on the paper insulation or copper conductor of the transformer. Created conductive paths between the windings can initiate turn-to-turn breakdown and failure of transformer. Several technological procedures have been developed as a solution for oil corrosivity. The application of desulfurization technology developed by the Electrical Engineering Institute ‘Nikola Tesla’ enables efficient removal of DBDS and aging products from mineral insulation oils.